Strategi optimalisasi jalur hijau dalam peningkatan potensi sekuestrasi CO2 (studi kasus: Jalan Jagir Wonokromo) - Salamah, Shalzafatihah; Cahyonugroho, Okik Hendriyanto (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Jalan Jagir Wonokromo in Surabaya City, East Java is a secondary arterial road with an average traffic density of 120,000 units per day and is surrounded by office, residential and commercial areas. The following conditions cause a lot of CO2 emissions resulting from anthropogenic activities that occur. The green line is the right solution and mitigation in tackling this problem, so it is important to know the ability to absorb CO2 from vegetation and the optimization strategy that can be applied. The research was conducted in the range from March to April 2023 with observations of composition and vegetation components as the basis for estimating carbon uptake using an allometric equation approach. Based on the research conducted, the CO2 absorption capability of the Jagir Wonokromo green line vegetation is 250,63 ton CO2-eq/year, which is a sufficient amount for CO2 absorption needs at that location. The optimization strategy undertaken includes intensification, extensification and mitigation.